Factors Affecting the Fiscal Independence of District City In East Java - Mudrosanto, Iswadi; Ananda, Candra Fajri; Susilo, Susilo (International Journal of Social and Local Economic Governance, 2020)
The fiscal independence can be understood as the allocation of the right to decide the amount and structure of the revenues and expenditures, the planning and also the execution of budgets. Furthermore, the ratio of local own revenue to total regional revenue not only reflects the financial condition but also a measure of independence, the ability to meet own needs, the ability to invest and also reflect the potency of economy. This study aims to analyze the effect of capital expenditure, investment, household consumption, and labor toward economic growth and to analyze the effect of economic growth towards the fiscal independence. This research used panel data which used the unit of analysis the districts and cities in East Java Province in the period of 2010 to 2014. This research used Simultaneous Equation Analysis Model with Two Stage Least Square (2SLS) method. The empirical results revealed that partially capital expenditure has a negative effect towards economic growth, investment and household consumption have a positive and significant effect toward economic growth, while labor insignificantly affect towards economic growth. Meanwhile simultaneously, capital expenditure, investment, household consumption, and labor have a positive and significant effect towards economic growth. Furthermore, the empirical results revealed that economic growth has a positive and significant effect towards the fiscal independence.